2008
DOI: 10.1007/s00253-008-1475-5
|View full text |Cite
|
Sign up to set email alerts
|

Homologous cloning, expression, and characterisation of a laccase from Streptomyces coelicolor and enzymatic decolourisation of an indigo dye

Abstract: The lack of a commercially available robust and inexpensive laccase is a major barrier to the widespread application of this enzyme in various industrial sectors. By using an efficient system developed in Streptomyces lividans, we have produced by homologous expression 350 mg L(-1) of a bacterial laccase with a high purity and without any extensive purification. This is the highest production yield reported in the literature for a bacterial laccase. The secreted enzyme achieved oxidation under a wide pH range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(78 citation statements)
references
References 33 publications
3
74
0
1
Order By: Relevance
“…The optimal temperature was found as 70 °C. On the other hand, at 30 °C, the enzyme was stable for more than a week and its half-life was longer than 8 h. The K m , V max , k cat , and k cat K m -1 values of the recombinant laccase were identified as 0.137 mM, 288.6 µmol min -1 L (Bento et al, 2005) and Streptomyces lividans (Dubé et al, 2008)], and plants [Arabidopsis thaliana (Wang et al, 2004) and Oryza sativa (de Wilde et al, 2008)]. Among those organisms, yeasts are usually more attractive hosts for heterologous protein production because of their faster microbial growth and ease of gene manipulation, along with the ability to perform posttranslational modifications.…”
Section: Introductionmentioning
confidence: 94%
“…The optimal temperature was found as 70 °C. On the other hand, at 30 °C, the enzyme was stable for more than a week and its half-life was longer than 8 h. The K m , V max , k cat , and k cat K m -1 values of the recombinant laccase were identified as 0.137 mM, 288.6 µmol min -1 L (Bento et al, 2005) and Streptomyces lividans (Dubé et al, 2008)], and plants [Arabidopsis thaliana (Wang et al, 2004) and Oryza sativa (de Wilde et al, 2008)]. Among those organisms, yeasts are usually more attractive hosts for heterologous protein production because of their faster microbial growth and ease of gene manipulation, along with the ability to perform posttranslational modifications.…”
Section: Introductionmentioning
confidence: 94%
“…Relatively few bacterial laccases have been studied with respect to their ability to degrade azo dyes (Pereira et al, 2009;Singh et al, 2007). However, laccases produced by Streptomyces are reported to be effective for the decolorization of textile dyes (Dube et al, 2008;Lu et al, 2013;Molina-Guijarro et al, 2009). Gottlieb et al (2003) demonstrated the usefulness of a laccase enzyme produced by Streptomyces cyaneus CECT 3335.…”
Section: Oxidative Enzymesmentioning
confidence: 99%
“…33 On the other hand, recombinant production of Streptomyces coelicolor laccase (SLAC) in Streptomyces lividans has yielded considerable large amount of laccase (350 mg l -1 ) with high purity. 34 The laccase from the ligninolytic fungus Cyathus bulleri has been just recently expressed in E. coli making it the first fungal laccase to be expressed in a bacterial host. 35 A collection of references on recombinant expression of laccases in bacterial hosts is available in Table 1.…”
Section: Laccase Recombinant Expressionmentioning
confidence: 99%